The GRE and Students With Disabilities: A Validity Study at 10 Universities. (January 2020) - Ling, Guangming; Buzick, Heather; Belur, Vinetha
We evaluated the validity of using the GRE General Test to assist with graduate school admissions for individuals with disabilities. We studied a sample of 16, 239 graduate students from 10 U.S. research universities in three groups: students without any reported disabilities, students who reported disabilities and took the computer-delivered GRE with accommodations, and students who reported disabilities but took the computer-delivered GRE without accommodations. We examined differential prediction using multilevel modeling and residual analyses. The results revealed that the first-year graduate grade point average of students with disabilities was neither over- nor underpredicted by more than one tenth of a point on the 0- to 4-grading scale. However, variations on the magnitude and direction of differential prediction existed among students with different types of disabilities. We discuss data collection needs and research on students with disabilities attending graduate and professional schools.